2017
DOI: 10.3892/ijmm.2017.2921
|View full text |Cite
|
Sign up to set email alerts
|

SphK1 modulates cell migration and EMT-related marker expression by regulating the expression of p-FAK in colorectal cancer cells

Abstract: Sphingosine kinase 1 (SphK1) plays an important role in colorectal carcinoma metastasis. However, whether SphK1 modulates epithelial-mesenchymal transition (EMT)-related marker expression and the underlying mechanisms remain unclear. In this study, in order to clarify this issue, we used various colorectal cancer (CRC) cell lines, Caco2, HT29, RKO and HCT116. Each of the cell lines was divided into 3 groups as follows: the control group, SKI-Ⅱ (SphK1 inhibitor) group and PF-562271 [focal adhesion kinase (FAK) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 40 publications
6
26
0
Order By: Relevance
“…Our study found that, stimulation of A549 cancer cells with IGF-1 induced overexpression and activation of SphK1, decreased E-cadherin expression and increased expression of N-Cadherin, vimentin and fibronectin, which were dependent on SphK1 activity, while SKI-II, the specific inhibitor of SphK1, could suppress the above effects. These results are consistent with the findings of a previous study, suggesting that SphK1 modulates EMT in colorectal cancer cells [22].…”
Section: Discussionsupporting
confidence: 93%
“…Our study found that, stimulation of A549 cancer cells with IGF-1 induced overexpression and activation of SphK1, decreased E-cadherin expression and increased expression of N-Cadherin, vimentin and fibronectin, which were dependent on SphK1 activity, while SKI-II, the specific inhibitor of SphK1, could suppress the above effects. These results are consistent with the findings of a previous study, suggesting that SphK1 modulates EMT in colorectal cancer cells [22].…”
Section: Discussionsupporting
confidence: 93%
“…With respect to the EMT process, E-cadherin is deemed as an typical anti-EMT marker while N-cadherin and Vimentin are pro-EMT markers in cancer cells. 24,25 Through the analysis of Western blotting, we found the E-cadherin protein level was elevated but N-cadherin and Vimentin exhibited the opposite trend after circ_0025033 was knocked down in A2780 and SKOV3 cells ( Figure 2G). Hence, circ_0025033 knockdown impeded the progression of OC cells in vitro.…”
Section: Circ_0025033 Knockdown Reduced Cell Viability Migration Inmentioning
confidence: 99%
“…It is known that Sphk1 is overexpressed in colorectal cancer tissues and cell lines, and the upregulation of Sphk1 is well correlated poor survival, mainly due to metastasis to lymph node, liver, and other organs. Indeed, one study showed that colon cancer with metastasis exhibited higher expression of Sphk1/S1P than those without metastasis, and another study showed that the expression levels of Sphk1, the focal adhesion kinase (FAK) pathway, intercellular adhesion molecule 1 (ICAM1), and vascular cell adhesion molecule 1 (VCAM1) were higher in colorectal cancers in comparison with their adjacent non-cancer tissues [ 56 , 57 ]. Moreover, the expression of Sphk1 was significantly correlated with the expression of FAK or p-FAK, and the co-expression of Sphk1, FAK, and p-FAK was significantly associated with colorectal cancer histopathological grades, Dukes’ stages, lymph node metastasis, and distant metastasis [ 40 , 56 ].…”
Section: Sphk1/s1p and Cancer Metastasismentioning
confidence: 99%
“…In contrast, knocking down SphK1 by shRNA targeting human Sphk1 suppressed cancer cell viability and invasiveness, but facilitated cell apoptosis. The expression levels of FAK, p-FAK, ICAM1, and VCAM1 were also upregulated with the overexpression of Sphk1 but downregulated with the reduction of Sphk1 in colon cancer cells [ 57 ]. These findings indicate that Sphk1 plays a critical role in colorectal cancer initiation and progression in vivo and regulates colon cancer cell proliferation, apoptosis, and invasion in vitro, which was through FAK pathway, ICAM-1, and VCAM.…”
Section: Sphk1/s1p and Cancer Metastasismentioning
confidence: 99%